Investigation of Attitudes Towards Exercise Behavior Changes of Adults Registered with Fitness and Activity Centers under the COVID-19 Lockdown - Nevzat Demirci; Pervin Toptaş Demirci; Bojan Bjelica; Erkan Güven (JUMORA: Jurnal Moderasi Olahraga, 2022)
In this article, the authors aim to examine the attitudes towards exercise behavior changes of adults who are registered to Fitness and Activity Centers under the COVID-19 Quarantine and cannot routinely go to gyms due to quarantine. Method; It consisted of a total of 120 individuals, 40 women and 80 men, between the ages of 18-55, registered to fitness and activity centers. The participants were selected from those who went to the gym for at least 45 minutes a day, 3 days a week for at least 6 months, and did fitness exercises for at least 6 months before the quarantine. The experiential and behavioral attitudes of the participants regarding the benefits of exercise were determined by the Exercise Change Processes Scale (EDSS). The components of experiential and behavioral processes are determined with a 5-point Likert-type scale consisting of 28 questions. According to the findings; There was no significant difference between men and women in the experiential sub-dimension and the behavioral sub-dimension, which includes helping relationships and empowering management processes (P>0.05). On the other hand, it was determined that there was a significant difference between the behavioral sub-dimension components of opposite and opposite situation, self-liberation and stimulus control, and total awareness levels between men and women (P<0.05, P<0.01). As a result, it can be argued that unlike the months-long quarantine effectively controlling the spread of the COVID-19 pandemic, it does not have a positive contribution to the exercise behavior change process. Keywords: COVID-19, Fitness, Exercise Behavior , lockdown